Thermal plasma of electric arc discharge in air between composite Cu-C electrodes - Veklich, A.; Fesenko, S.; Boretskij, V.; Cressault, Y.; Gleizes, A.; Teulet, Ph.; Bondarenko, Y.; Kryachko, L. (Вопросы атомной науки и техники, 2014)
The complex technique of plasma property studies is suggested. As the first step the radial profiles of temperature and electron density in plasma of free burning electric arc discharge in air between Cu-C composite and brass electrodes, as well as copper electrodes in air flow, were measured by optical emission spectroscopy techniques. As the next step the radial profiles of electric conductivity of plasma mixture were calculated by solution of energy balance equation. The electron density is obtained from electric conductivity by calculation in assumption of local thermodynamical equilibrium in plasma.